Electrospinning of non-ionic cellulose ethers/polyvinyl alcohol nanofibers: characterization and applications - Wali, Ashwini; Zhang, Yucheng; Sengupta, Poulomi; Higaki, Yuji; Takahara, Atsushi; Badiger, Manohar V. (Carbohydrate Polymers, 2018)
The morphology of spin-coated films and electrospun fibers of ethyl hydroxy ethyl cellulose (EHEC), hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) and their blends with Poly(vinyl alcohol) (PVA) was examined by AFM, SEM and contact angle measurements. These polysaccharides upon blending with PVA exhibited smooth surface which was evidenced by Atomic Force Microscopy (AFM) observation. The electrospinnability of above polysaccharides with PVA was demonstrated for the first time. The oriented fibers could be obtained using a rotating disc collector. Contact angles of spin-coated films and electrospun fibers were discussed in terms of hydrophobicity and wetting characteristics. Further, The nanofibers of EHEC/PVA were in-situ crosslinked using citric acid and were used for controlled release of an antibacterial drug, Chlorhexidine Digluconate (ChD). In-vitro studies of cytotoxicity, cell growth and cell proliferation were performed using L929 mouse fibroblast cells. These nanofiber mats show potential in drug delivery and as scaffolds in tissue engineering applications.
Keywords: cellulose; drug delivery; electrospinning; Ethyl hydroxy ethyl cellulose; Hydrophobically modified ethyl hydroxy ethyl; scaffold; Spin coating

Vivo wound healing performance of halloysite clay and gentamicin-incorporated cellulose ether-PVA electrospun nanofiber mats - Wali, Ashwini; Gorain, Mahadeo; Inamdar, Satish; Kundu, Gopal; Badiger, Manohar V. (ACS Applied Bio Materials, 2019)
Wound healing is a dynamic and complex process that requires a suitable environment to enhance the rapid healing process. In this context, fabrications of nanofibrous materials with antibiotic and antibacterial properties are becoming extremely important. In this present work, we report on the fabrication and characterization of electro-spun cellulose ether-PVA nanofiber mats loaded with halloysite clay (HNT) and gentamicin sulfate (GS) for faster wound healing applications. The morphology of nanofiber mats was examined by SEM and TEM. The average diameter of the nanofiber mats were in the range of 325 ± 30 nm. The physicochemical characterizations were done by FT-IR and XRD, which reveal the presence of HNT and GS into the nanofibers. The incorporation of halloysite gave good mechanical strength to the nanofiber mats. Swelling studies indicated the hydrophilicity of the mats. In vitro studies revealed that HNTs are nontoxic to L929 fibroblast cells and also promote cell growth and proliferation. The antibacterial property of HNT was also studied. The slow release of GS from the nanofiber mats was observed for a period of 18 days. The in vivo wound healing studies on the wistar rats for 21 days revealed the wound healing faster within 2 weeks by the incorporation of HNT and GS into the nanofiber mats and hence these nanofiber mats show great potential in acute and chronic wound healing applications.

Silver nanoparticles in electrospun ethyl hydroxy ethyl cellulose-PVA Nanofiber: synthesis, characterization and wound dressing applications - Wali, Ashwini; Gorain, Mahadeo; Kundu, Gopal; Badiger, Manohar (Carbohydrate Polymer Technologies and Applications, 2024)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Electrospinning is a simple, cost-effective technique and a reproducible process for both synthetic and <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/natural-polymer" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about natural polymers from ScienceDirect's AI-generated Topic Pages">natural polymers. It is found to be an attractive tool for various applications in biomedical engineering, filtration, protective clothing, catalysis reactions and sensors. Non-ionic cellulose ethers namely Ethyl Hydroxy <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/ethyl-cellulose" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about Ethyl Cellulose from ScienceDirect's AI-generated Topic Pages">Ethyl Cellulose (EHEC) is an important <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/polysaccharide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about polysaccharide from ScienceDirect's AI-generated Topic Pages">polysaccharide which is non-toxic, biocompatible and biodegradable and finds applications as thickening/rheology control agents in paints, cosmetics, detergents, oil recovery and also in the biomedical area. Poly (vinyl alcohol) (PVA) is a semi-crystalline <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/hydrophilic-polymers" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about hydrophilic polymer from ScienceDirect's AI-generated Topic Pages">hydrophilic polymer which is highly biocompatible and non-toxic having good thermal and mechanical properties and also high water solubility. Silver shows powerful antimicrobial activity and is non-toxic. It has been used to cure severe burns and chronic ulcers for many decades and is extensively used as an additive in various fields like prostheses, burn treatment, catheters, vascular grafts, dental resin components, ion exchange fibers, <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/stainless-steel" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about stainless steel from ScienceDirect's AI-generated Topic Pages">stainless steel materials, human skin and coating of <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/medical-device" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about medical devices from ScienceDirect's AI-generated Topic Pages">medical devices. In the present work, EHEC/PVA <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers embedded with silver <a class="topic-link" href="https://www.sciencedirect.com/topics/chemical-engineering/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanoparticles from ScienceDirect's AI-generated Topic Pages">nanoparticles (AgNPs) are studied for their <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/antibacterial-activity" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about antibacterial activity from ScienceDirect's AI-generated Topic Pages">antibacterial activity using both gram positive and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/gram-negative-bacterium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about gram negative bacteria from ScienceDirect's AI-generated Topic Pages">gram negative bacteria. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers show increase in <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/tensile-property" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about tensile properties from ScienceDirect's AI-generated Topic Pages">tensile properties with the addition of silver nano-particles. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/silver-nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about AgNPs from ScienceDirect's AI-generated Topic Pages">AgNPs embedded EHEC/PVA nanofiber mats having 0.5% AgNPs were found to enhance the <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound-healing" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wound healing from ScienceDirect's AI-generated Topic Pages">wound healing with no scar formation in <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wistar-rat" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wistar rats from ScienceDirect's AI-generated Topic Pages">wistar rats. The biological <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vitro<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> and <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vivo<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> studies support the potential of EHEC based <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers as excellent bio-materials for the treatment of severe burns and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wounds from ScienceDirect's AI-generated Topic Pages">wounds. To the best of our knowledge, this is the first report on the electrospinning of EHEC/PVA nanofibers for wound healing applications.

Microgels of hydrophobically modified-ethyl hydroxy ethyl cellulose (HM-EHEC) with 5-flurouracil for drug delivery applications - Wali, Ashwini; Badiger, Manohar (Research Journal of Biotechnology, 2025)
The polysaccharides (e.g. celluloses and proteins) which form the basic building blocks of life, are gaining increased interest in recent times for researchers to develop newer health care products from renewable bio-polymers which are cheaper and easily available with different desirable properties. Gels are highly swollen three dimensional networks of hydrophilic polymers cross-linked by physical or chemical interactions. Our focus was to design and develop a novel microgel system which would effectively deliver the anti-cancer drug to the targeted site by slow and sustained release for longer times. The water soluble hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) biopolymer was used in the synthesis of microgels by Michael-type addition reaction between the primary hydroxyl groups of HM-EHEC and Divinyl sulphone (DVS) crosslinker using water-in-oil emulsion technique. The microgels obtained were spherical in shape having flower type morphology with average size of 5 to 8 μm. The anti-cancer drug 5-Flurouracil (5-FU) drug was successfully incorporated and around 56% of the 5-FU was released in 72 hours with a loading efficiency of 95%. The cell viability (MTT assay) studies confirmed the cycto-toxicity on the MDA-MB 231 breast cancer cell line. There was an increase in the cell death with increase in the concentration of microgel containing drug concentration. The HM-EHEC microgels could be effectively used in the form of a topical cream in the skin and breast cancer for on-site slow and targeted delivery.